Impact of Hospital Nurses’ Perception on Clinical Alarms and Patient Safety Culture on Alarm Management Practice - Lee, Soo-Joung (Int J Environ Res Public Health, 2021)
This study aimed to identify the impact of nurses’ perception of clinical alarms and patient safety culture on alarm management. Additionally, we aimed to describe the importance of clinical alarm issues. The data were collected from 21 August to 10 September 2020. The study participants were 116 nurses working in a tertiary acute care hospital in Korea. The self-report questionnaire included general characteristics, clinical alarm issues, nurses’ alarm perception, patient safety culture, and alarm management practice. The mean age of nurses was 28.04 ± 4.06 years, with 5.71 ± 4.35 years of total clinical experience. For the importance of alarm issues, frequent false alarms leading to reduced attention or response was the most important issue. Hierarchical linear regression analysis revealed that a higher level of nurses’ perceived patient safety culture was the strongest predictor of better alarm management practice (p < 0.001), followed by their perception of clinical alarms (p = 0.034). In addition, female nurses (p = 0.004), charge nurses (p = 0.013), and nurses who work less than 40 h per week (p = 0.008) were more likely to work better in alarm management practice. Future studies are needed to develop standardized alarm management guidelines by improving nurses’ positive perceptions of clinical alarms and patient safety culture.